MUSIK BAS DI KECAMATAN BARAKA KABUPATEN ENREKANG (SUATU TINJAUAN ORGANOLOGI) - Soekarno B. Pasyah (Universitas Lancang Kuning, 2023)
This study aims to find out: 1). Background of Bass Music in Baraka District Enrekang District, 2). Procurement of materials and process of making bass instruments, 3). Function and tone system in a bass instrument in Baraka Sub-district of Erekang District. This research uses observation method, interview, documentation, and study of organology sciences, by collecting data from various relevant sources, then the researcher describes the problem solving validly and descriptively and then draws a conclusion by yielding data: 1). The birth of bass music in District Baraka Regency Enrekang around the 1940s under the colonists of Menado and Ambon. 2). The process of making instruments using traditional tools. 3). Function and tone system on the bass instrument.